Double phase transition in the triangular antiferromagnet Ba3CoTa2O9. (7th February 2017) - Ranjith, K M; Brinda, K; Arjun, U; Hegde, N G; Nath, R
Abstract: Here, we report the synthesis and magnetic properties of a new triangular lattice antiferromagnet Ba3 CoTa2 O9 . The effective spin of Co 2+ is found to be J = 1/2 at low temperatures due to the combined effect of crystal field and spin–orbit coupling. Ba3 CoTa2 O9 undergoes two successive magnetic phase transitions at T N 1 ≃ 0.70 K and T N 2 ≃ 0.57 K in zero applied field, which is typical for triangular antiferromagnets with the easy-axis magnetic anisotropy. With increasing field, the transition anomalies are found to shift toward low temperatures, confirming the antiferromagnetic nature of the transitions. At higher fields, the transition peaks in the heat capacity data disappear and give way to a broad maximum, which can be ascribed to a Schottky anomaly due to the Zeeman splitting of spin levels. The H − T phase diagram of the compound shows three distinct phases. The possible nature of these phases is discussed.